Determinants of the Investment Policy of the Insurance Guarantee Fund (IGF) - Bamber , Bogusław (Studia Oeconomica Posnaniensia, 2015)
IGF finances its activities with means collected through two funds: the statutory fund and the assistance fund. Financial means accumulated in these funds are invested in different financial instruments through co-operating banks. The aim of this paper is to analyze IFG's investment activity as well as to assess it against the background of legal and financial market limitations, the financial investment strategies adopted and the condition of the money and capital markets in Poland. Further- more, the problem pertaining to IGF's investment policy benchmark is discussed.